1989
DOI: 10.3758/bf03202628
|View full text |Cite
|
Sign up to set email alerts
|

The generation effect extended: Memory enhancement for generation cues

Abstract: The generation effect is the greater memorability of a response that is actively produced (e.g., in answering a question from memory) than one that is more passively produced (as in reading the answer). The present three experiments addressed a question that is critical to the theoretical interpretation of the generation effect: Is memory enhanced for the cues that are used to elicit generated responses? Using incidental learning procedures, Experiments 1 and 2 gave an affirmative answer (although the effect w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
35
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 18 publications
5
35
1
Order By: Relevance
“…They therefore prudently deferred drawing any firm conclusion as to whether or not generation also increases recall of the cue words, pending further replication. Recently, however, Greenwald and Johnson (1989) reported a generation effect for the recall of the stimulus terms of related pairs when they were cued with the response terms. Their results are thus consistent with our proposed explanation for the lack of a context effect for generated items.…”
Section: Resultsmentioning
confidence: 99%
“…They therefore prudently deferred drawing any firm conclusion as to whether or not generation also increases recall of the cue words, pending further replication. Recently, however, Greenwald and Johnson (1989) reported a generation effect for the recall of the stimulus terms of related pairs when they were cued with the response terms. Their results are thus consistent with our proposed explanation for the lack of a context effect for generated items.…”
Section: Resultsmentioning
confidence: 99%
“…This difference between cued recall and recognition was critical to their theoretical argument. Indeed, they argued that the only other relevant study (Greenwald & Johnson, 1989, Experiment 2) had found a significant generation effect for cue words in recognition because cued recall had preceded recognition, thereby contaminating it. Although we cannot dispute their criticism, the same claim cannot be applied to the present experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Begg, Snider, et al (1989) found no cases in which recall of contexts cued by generated targets exceeded recall of contexts cued by read targets. Greenwald and Johnson (1989) found a generation effect in recall of contexts, but the small effect was reliable only when experiments were combined, and there was a strong generation effect in memory for the targets; perhaps the generation effect in recall of contexts occurred because more of the targets were recognized when they were given as cues. McDaniel and Waddill (1990) found a more substantial effect, but there was no unique generation effect in recall of the contexts; there were strong effects of generation on recall of targets.…”
Section: Generated Targets Benefit From Generationmentioning
confidence: 99%
“…For example, recognition memory for horse is better if the original stimulus was tiger-h-r-e rather than tigerhorse, but recognition of tiger is equally good in both cases (Begg, Snider, et al, 1989;see also Slamecka & Graf, 1978). In two recent articles, generation effects have been reported for contexts (Greenwald & Johnson, 1989;McDaniel & Waddill, 1990): Greenwald and Johnson found a generation effect in recognition of contexts, but the recognition test followed a recall test; McDaniel and Waddill tested recognition of contexts unconfounded by a previous test, and did not find a generation effect. Hence, the generation effect in recognition is item-specific, and the target is the item.…”
Section: Generated Targets Benefit From Generationmentioning
confidence: 99%